2019
DOI: 10.1111/jvim.15582
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic use of tetrasodium ethylenediaminetetraacetic acid solution for treatment of subcutaneous ureteral bypass device mineralization in cats

Abstract: Background Subcutaneous ureteral bypass (SUB) device placement is an increasingly popular treatment option for decompression of ureteral obstruction in cats. Mineralization occlusion of the device occurs in a minority of cases but is the most common complication. Objective To evaluate a 2% tetrasodium ethylenediaminetetraacetic acid (tEDTA) solution for treatment of mineralization occlusion in cats with SUBs. Animals Six client‐owned cats (8 obstructed devices). Methods Case series. Each cat was found to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…As mentioned previously, published short-term postoperative complications include implant occlusion from blood clots and urolith material, device leakage, tube kinking, haemorrhage, dysuria and UTIs. 2 , 7 Mineralisation of the cystotomy tube is the most commonly reported long-term complication with known risk factors including the use of a small port, silicone-based catheters and postoperative ionised hypercalcaemia. 3 , 7 To our knowledge, at the time of publication, there have been no reported gastrointestinal complications relating to SUB implant systems or other ureteral decompressive surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned previously, published short-term postoperative complications include implant occlusion from blood clots and urolith material, device leakage, tube kinking, haemorrhage, dysuria and UTIs. 2 , 7 Mineralisation of the cystotomy tube is the most commonly reported long-term complication with known risk factors including the use of a small port, silicone-based catheters and postoperative ionised hypercalcaemia. 3 , 7 To our knowledge, at the time of publication, there have been no reported gastrointestinal complications relating to SUB implant systems or other ureteral decompressive surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 The most significant long-term complication is mineralisation of the SUB device, most commonly the cystostomy tube. 3,7 Other reported long-term complications include migration of the cystostomy catheter and extrusion of the SC access port. 8,9 To our knowledge, at the time of publication, there have been no reported long-term gastrointestinal complications with SUB system implantation in cats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a tetrasodium EDTA acid flush solution through the subcutaneous shunting port in order to demineralise and restore patency of the SUB device has already been established in veterinary medicine. 14 Moreover, the antimicrobial and anti-biofilm properties of EDTA in wounds and indwelling catheters have been studied. 1517 In a recent study, it was shown that the implementation of routine irrigation of the SUB device using tetrasodium EDTA solution appeared to decrease infection rates associated with SUB devices in cats.…”
Section: Discussionmentioning
confidence: 99%
“…1517 In a recent study, it was shown that the implementation of routine irrigation of the SUB device using tetrasodium EDTA solution appeared to decrease infection rates associated with SUB devices in cats. 14 However, large clinical studies are required to establish the effectiveness of tetrasodium EDTA acid flush solution to prevent and treat biofilms in SUB devices, and to manage chronic SUB system infections, before this becomes common practice in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%